Livestock revolution in tropical monsoon countries: some challenges and issues - Khan, Nizamuddin; Iqubal, Asif; Rehman, Anisur (Journal for Geography, 2011)
Livestock husbandry is one of the important demand driven sectors of agriculture in the world. It acts as a global resource in the form of food, income, nutrients, employment, insurance, clothing and others purposes. It plays a vital role in socio-economic development of the farmers. Demand of livestock products is increasing on account of increasing population, changing food habits of the middle class population and urbanization in developing Asian countries. This paper seeks to understand the pattern of growth of livestock number as well as their products and to identify the issues and challenges emerged on account of dynamics in livestock husbandry in Monsoon Asian countries. By analyzing the recorded data of FAO (Food and Agriculture Organization) in different years paper enables to state that all species of livestock showed positive growth rate with the exception of sheep and pigs. Now the livestock husbandry showing the structural change i.e. in general it is shifting from horizontal expansion to vertical expansion in most of the study region. The livestock improved tremendously and achieved a great success in raising livestock derived products. Various issues and challenges of livestock husbandry are now deserved for academic and scientific discussion as a result of livestock revolution in world in general and tropical monsoon countries in particular.